The Effect SME in Overcoming Poverty and Unemployment: Empirical Study of Makassar City, Indonesia - Dahliah, D.; Sidik Tjan, Yulianty; Rahmi, R. (Manunggal Halim Jaya, 2023)
This study aims to analyze whether Micro, small and medium enterprises (SME) have an effect in overcoming poverty levels in Makassar City; Whether Micro, small and medium enterprises have an effect in overcoming unemployment in Makassar City. This research is a quantitative approach, because this research is presented with numbers. This research was conducted in Makassar city and the research period was from May to November 2022. The data used to support this research is secondary data (Time Series) for 2010-2020. Data collection methods, namely: Observation, Documentation. The population in this study is data on the development of SME, the Poor Population and the Unemployment Rate in Makassar City, while the samples in this study are SME, the Poor Population and the Unemployment Rate in Makassar City in 2011-2021. Researchers also use a saturated sampling technique that uses all members of the population, the reason is because the data processed is in the form of a census which is already in the form of annual reports issued by related institutions. The data analysis method is regression analysis. The results of this study state that 1). SME also have a negative effect in overcoming or reducing poverty levels. In other words, the relationship between SME and Poverty has an opposite relationship. which means that the more micro, small and medium enterprises develop, poverty will decrease, so SME play a role in reducing poverty in Makassar City. 2). SME have a negative effect in overcoming or reducing the unemployment rate. In other words, the relationship between SME and the unemployment rate has an opposite relationship. which means that the more SME develop, the unemployment rate will decrease, so SME play a role in reducing the unemployment rate in Makassar City.